Pengaruh Kemampuan Adaptasi, Emotional Intelligence, Dan Kepuaasan Kerja Terhadap Kinerja Karyawan Perusahaan Tekstil Di Kabupaten Cirebon: - - Nadya Puspa Dewi Nadya; Zakiyatul Mufaqiroh (Economics and Digital Business Review, 2025)
This study aims to analyze the influence of adaptability, emotional intelligence, and job satisfaction on employee performance in textile companies in Cirebon Regency. In the era of global competition and the ever-evolving dynamics of the manufacturing industry, employees are required to be able to adapt, manage emotions effectively, and maintain a high level of job satisfaction to achieve optimal performance. This research uses a quantitative approach with a survey method involving 120 respondents who are employees from several selected textile companies. The data analysis technique employed is multiple linear regression to examine both the simultaneous and partial effects of the three independent variables on the dependent variable. The results show that adaptability, emotional intelligence, and job satisfaction simultaneously have a significant influence on employee performance. Partially, each variable also demonstrates a significant positive effect. Adaptability enables employees to respond flexibly to changes in the work environment, while emotional intelligence assists in stress management, communication, and interpersonal relationships. On the other hand, high job satisfaction contributes to increased motivation and productivity. These findings indicate that companies need to pay serious attention to the development of soft skills and employee well-being as part of their performance enhancement strategies. This study is expected to contribute to the human resource management literature and serve as a practical reference for policymakers in creating a work environment that is adaptive, supportive, and fulfilling. Keywords: Adaptability, Emotional Intelligence, Job Satisfaction